2007
DOI: 10.1175/jas4034.1
|View full text |Cite
|
Sign up to set email alerts
|

Extratropical–Tropical Interaction during Onset of the Australian Monsoon: Reanalysis Diagnostics and Idealized Dry Simulations

Abstract: The onset of the Australian monsoon is examined using (i) reanalysis data for seasons when enhanced observational networks were available and (ii) a 15-yr onset composite. Similar to previous findings, onset is characterized by a sudden strengthening and deepening in tropical westerly winds, which are overlain with upper-tropospheric easterlies. All onsets are preceded by up to a 7-day preconditioning period of enhanced vertical motion and moistening. During the transition season, the 6 weeks prior to onset, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
9
20
0
Order By: Relevance
“…Our argument is that a high latitude blocking can dynamically influence the formation of an area of weak shear over the subtropics. This is similar, for instance, to the process described by Davidson et al (2007), when the high latitude flow over the Indian Ocean was found to potentially influence the outcome of the monsoon trough in the Australian region. In the case of Catarina, a likely mechanism is a slow propagation of weak shear from the south as the blocking builds up.…”
Section: The 'South Atlantic Index' and High-latitude Interactionssupporting
confidence: 76%
See 1 more Smart Citation
“…Our argument is that a high latitude blocking can dynamically influence the formation of an area of weak shear over the subtropics. This is similar, for instance, to the process described by Davidson et al (2007), when the high latitude flow over the Indian Ocean was found to potentially influence the outcome of the monsoon trough in the Australian region. In the case of Catarina, a likely mechanism is a slow propagation of weak shear from the south as the blocking builds up.…”
Section: The 'South Atlantic Index' and High-latitude Interactionssupporting
confidence: 76%
“…At present, there is no climatology of hybrid and transitioning systems in the SA, and their behaviour is still poorly understood in the SH, although some insights have recently been gained in the Australia region (Davidson et al, 2007), where both tropical and extra-tropical transitions seem to be very important mechanisms. Future studies addressing these patterns in more detail are much needed, in particular, on the basis of a more general largescale approach in order to further explore and test the interactions proposed here.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…This is seen as a series of troughs and ridges (marked with symbols 'T' and 'R') emanating from the cyclogenesis region and extending northeastwards to low latitudes. This structure is very similar to that described in Davidson et al (2007) during onset events. The proposed mechanism, which still requires further consolidation, is that amplifying Rossby Waves are refracted towards the tropics by the subtropical jet and as part of the wave propagation, the strengthening upper level tropical ridge, with accelerating upper level easterly winds on its northern side, influence large-scale tropical cloudiness and the monsoon.…”
Section: Evolution Of Tracy's Large Scale Environmentsupporting
confidence: 85%
“…Cross-checking against more recently-available ERA40 data was conducted to confirm consistency of diagnostic results. Similar to the findings in Davidson et al (2007), apart from some differences in the moisture analysis and in the intensity of the diagnosed ascent field, the data sets are very similar. Note that for simulations, because of the diabatic initialization used here (see description below), there is less sensitivity to the vertical motion and moisture fields contained in the raw re-analysis data.…”
Section: Data and Numerical Systemssupporting
confidence: 78%
See 1 more Smart Citation